Can Fraudulent Cues Be Transmitted by Innocent Participants?. Issue 1 (2nd January 2018) - Murphy, Pamela R.; Purda, Lynnette; Skillicorn, David
ABSTRACT: The authors explore whether and how linguistic indicators of fraud make their way into the Management Discussion & Analysis (MD&A) section of financial reports. Although research has shown that word choice and tone can help identify fraudulent financial reports, it is as yet unclear how this occurs when these reports are written by many individuals, some of whom are unaware that financial misrepresentation is occurring. Through an examination of industry recommendations and interviews with individuals experienced in writing the MD&A section, the authors confirm that many hands are involved in drafting this portion of financial reports. The authors then structure an experiment, using a real fraud case, that asks participants to write an MD&A from truthful prior U.S. Securities and Exchange Commission filings and a memo from the CFO with suggestions of what to say in the current period MD&A. Unbeknownst to participants the CFO memo was created using phrases from financial statements subsequently identified to be fraudulent. The authors find that individuals do unwittingly write MD&A associated with fraudulent financial statements with relatively little suspicion and that linguistic cues contained in the CFO memo are transmitted to the ultimate MD&A through naive and innocent participants.